Accuracy of centre of pressure gait measurements from two pressure-sensitive insoles - Weizman, Y.; Tan, A. M.; Fuss, F. K. (Proceedings, 2018)
Footwear-based wearable applications are relevant to numerous fields and have great commercial and clinical potential. However, scientifically validated, reliable data on these devices is largely missing. Centre of pressure (COP) is an important and common factor for measuring balance and gait and hence the validity of such devices is essential for reading accurate data. This study aims to investigate COP accuracy of an existing system, Pedar (PE), and a newly designed Smart Insole (SI) using a force plate (FP). This was done by means of COP data noise (R2), and gradient of the fit function (k). For the SI, the maximum COPx and COPy data achieved R2 values of 0.7837 and 0.9368 and k values of 0.8867 and 0.8538 respectively when compared with the FP. Conversely, the Pedar achieved R2 values of 0.8409 and 0.9401 and k values of 1.0492 and 1.08 when compared with the FP respectively.